Strategi Pembelajaran Kolaboratif Untuk Meningkatkan Pemahaman Siswa Terhadap Ajaran Kristen - Dominius, Fransiskus; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
Christianity learning is an important aspect in shaping students' character and faith. However, in its implementation, there is often a lack of active student participation as well as a deep understanding of the material being taught. One solution that can be applied is the use of collaborative learning strategies. This strategy involves students actively in the learning process through group work, discussions, and project-based activities. The purpose of this research is to examine various collaborative learning strategies that are effectively applied in learning Christian religious education, as well as providing an understanding of the benefits and impact on improving student understanding. The methods used in this research are literature study and observation of the implementation of collaborative learning strategies in several Christian religious education classes. The results showed that collaborative learning is able to increase students' motivation, participation, and understanding of Christian teaching materials. In conclusion, collaborative learning strategies are very relevant and effective to use in the context of Christian religious education to create meaningful and enjoyable learning for students.